Modelling non-alcoholic fatty liver disease in human hepatocyte-like cells. (21st May 2018) - Lyall, Marcus J.; Cartier, Jessy; Thomson, John P.; Cameron, Kate; Meseguer-Ripolles, Jose; O'Duibhir, Eoghan; Szkolnicka, Dagmara; Villarin, Baltasar Lucendo; Wang, Yu; Blanco, Giovanny Rodriguez; Dunn, Warwick B.; Meehan, Richard R.; et al.
Abstract : Non-alcoholic fatty liver disease (NAFLD) is the most common cause of liver disease in developed countries. An in vitro NAFLD model would permit mechanistic studies and enable high-throughput therapeutic screening. While hepatic cancer-derived cell lines are a convenient, renewable resource, their genomic, epigenomic and functional alterations mean their utility in NAFLD modelling is unclear. Additionally, the epigenetic mark 5-hydroxymethylcytosine (5hmC), a cell lineage identifier, is rapidly lost during cell culture, alongside expression of the Ten-eleven-translocation ( TET ) methylcytosine dioxygenase enzymes, restricting meaningful epigenetic analysis. Hepatocyte-like cells (HLCs) derived from human embryonic stem cells can provide a non-neoplastic, renewable model for liver research. Here, we have developed a model of NAFLD using HLCs exposed to lactate, pyruvate and octanoic acid (LPO) that bear all the hallmarks, including 5hmC profiles, of liver functionality. We exposed HLCs to LPO for 48 h to induce lipid accumulation. We characterized the transcriptome using RNA-seq, the metabolome using ultra-performance liquid chromatography-mass spectrometry and the epigenome using 5-hydroxymethylation DNA immunoprecipitation (hmeDIP) sequencing. LPO exposure induced an NAFLD phenotype in HLCs with transcriptional and metabolomic dysregulation consistent with those present in human NAFLD. HLCs maintain expression of the TET enzymes and have a liver-like epigenome. LPO exposure-induced 5hmC enrichment at lipid synthesis and transport genes. HLCs treated with LPO recapitulate the transcriptional and metabolic dysregulation seen in NAFLD and additionally retain TET expression and 5hmC. This in vitro model of NAFLD will be useful for future mechanistic and therapeutic studies. This article is part of the theme issue 'Designer human tissue: coming to a lab near you'.